THE The Philosophy of Time In Surah Al- ‘Asr: A Textual Analysis In Its Interpretation Diversities - Yaakub, Muhamadul Bakir; Othman, Khatijah; M.Bakir, Afeeq Busyra (MAQOLAT: Journal of Islamic Studies, 2025)
The contemporary global web applications have contributed to the evolution of the current generation's understanding of Islamic concepts and philosophies. This article examines the fundamental understanding of time, its meaning, and its application as highlighted in Surah al- ‘Asr, through the lens of Islamic psycho-social measures. Numerous authors have emphasized the importance of focusing on the theoretical concept of time and its utilization based on the principles derived from original Islamic sources. This study focuses on the philosophical understanding based on Surah al- ‘Asr. The analysis is based on the textual of the Surah that aims to understand the context of the word meaning, to examine its content from textual perspective, and how the influence of psycho-social aspects of education and culture varies in interpretation. Its nature is observed throughout its Arabic linguistic patterns and structures, in which its philosophical principles are clearly identified within the textual discourse. The argument of this study is driven by a systematic textual analysis as a fundamental approach to determine the meaning of a word within its textual context. At its essence, Surah al- ‘Asr is both a reminder of time’s brevity and a call to action, fostering spiritual growth, discipline, and awareness of life’s transience. ‘Asr prayer divides the day, inspiring reflection, renewal, and purposeful preparation for the night. End of the daytime should be used wisely to complete tasks and prepare for the evening through cleaning, resting, and performing Maghrib prayer. During the analytical process, we observed how a text interpreter might reach the ultimate meaning of a text, uncovering its intended significance. Hypothetically, contemporary Islamic educational and translational institutions should implement appropriate adjustments directly to the text. These adjustments are necessitated by the technological advancements that influence the development of users' knowledge and comprehension of Islamic texts and resources.